2016
DOI: 10.1038/srep25656
|View full text |Cite
|
Sign up to set email alerts
|

Urinary arsenic profiles reveal exposures to inorganic arsenic from private drinking water supplies in Cornwall, UK

Abstract: Private water supplies (PWS) in Cornwall, South West England exceeded the current WHO guidance value and UK prescribed concentration or value (PCV) for arsenic of 10 μg/L in 5% of properties surveyed (n = 497). In this follow-up study, the first of its kind in the UK, volunteers (n = 207) from 127 households who used their PWS for drinking, provided urine and drinking water samples for total As determination by inductively coupled plasma mass spectrometry (ICP-MS) and urinary As speciation by high performance … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
33
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 47 publications
(34 citation statements)
references
References 50 publications
1
33
0
Order By: Relevance
“…These findings shed light, at least in part, on low-level As exposure induced health risks, suggesting that a consideration of downward revision of the WHO provisional guide value may be indicated to protect better human health and to reduce the economic burden arising from CVD related outcomes, even in countries such as the UK, where relatively few individuals consume drinking water with more than 10 µg/L As [39], but over 20 million people consume drinking water with between 1 µg/L As and 10 µg/L As [38]. Future carefully designed larger-scale perspective studies with sufficient individual data of CVD risk and low level environmental As exposure from different sources are necessary to evaluate the association between As exposure and increases in CVD risk.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…These findings shed light, at least in part, on low-level As exposure induced health risks, suggesting that a consideration of downward revision of the WHO provisional guide value may be indicated to protect better human health and to reduce the economic burden arising from CVD related outcomes, even in countries such as the UK, where relatively few individuals consume drinking water with more than 10 µg/L As [39], but over 20 million people consume drinking water with between 1 µg/L As and 10 µg/L As [38]. Future carefully designed larger-scale perspective studies with sufficient individual data of CVD risk and low level environmental As exposure from different sources are necessary to evaluate the association between As exposure and increases in CVD risk.…”
Section: Discussionmentioning
confidence: 88%
“…Due to the recent publication of a number of key epidemiological studies [36] building upon our recent research in exposure science [37][38][39], we aimed to use meta-analysis to determine quantitatively the magnitude of increased CVD risks for the general population exposed at As concentrations lower than the WHO provisional guideline value for drinking water of 10 µg/L. We have also included some CVD biomarkers in the evaluation.…”
Section: Introductionmentioning
confidence: 99%
“…to 3280 ± 60 p.p.m., consistent with the mining activities at the site and also with pedogenesis of the country rock, which has been reported to contain the arsenate minerals scorodite (FeAsO 4 8 which is significantly above the World Health Organisation drinking water limit of 0.1 p.p.m. 9 To our knowledge, despite detailed investigation of uranium at the site, the migration of arsenic to the River Fal has not previously been investigated.…”
Section: Resultsmentioning
confidence: 99%
“…Significantly arsenic in the domestic drilled bedrock wells more than water from municipal sources (Qiang et al 2009). Middleton et al 2016 reported that 5% private water supplies of 497 wells in Cornwall, South West England exceeded the WHO As standard of 10 μg/L.…”
Section: The Situation In the Mekong River Deltamentioning
confidence: 99%